Analisis Rasio Keuangan Anggaran Pendapatan dan Belanja Daerah Untuk Menilai Kinerja Keuangan Pemerintah Daerah Kabupaten Pesawaran Tahun 2010-2014 - Khairudin KHAIRUDIN; Aminah AMINAH (Jurnal Akuntansi dan Keuangan, 2017)
This study aims to assess the financial performance of the local government district Pesawaran using financial ratio analysis of budget revenue and expenditure Pesawaran District 2010-2014. The analysis is used to analyze financial performance is by calculating the ratio of the area Independence , Ratio Effectiveness , Efficiency Ratio . While the analysis is used to analyze the financial capacity of the area is by counting Share and Growth , Financial Capability Map.  Based on analysis of the financial performance of it can be concluded , the average ratio of local independence Pesawaran District that are in the relationship patterns instructive . But the level of effectiveness of financial management Pesawaran District is fairly effective . While the level of efficiency of financial management is relatively less efficient , the financial condition of local government district Pesawaran still not ideal. Can be seen from the average Share and Growth. Position Pesawaran District is in quadrant II .